PENGARUH MOTIVASI, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN LABUHANBATU - Ahmad Rivai Siregar; Ali Sahbana Edi Lubis; Syafrizal Effendi; Sondang Roma Elda T; Delita . (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2021)
The problem of this research is: How does the motivation, organizational culture and work discipline on the performance of employees. This study aims to determine the effect of motivation, organizational culture and work discipline on employee performance. With the probability sampling technique determined by the Slovin  formula,  the  sample in  this  study  was 64  people.  The motivation variable partially has a positive influence on employee performance; The organizational  culture variable partially  has  a  positive influence on  employee performance; The work discipline variable partially has a positive influence on employee performance; Motivation, organizational culture and work discipline simultaneously   have   a   positive   and   significant   influence   on   employee performance.